2017
DOI: 10.23918/ijsses.v4i2sip98
|View full text |Cite
|
Sign up to set email alerts
|

Using Discovery Learning to Encourage Creative Thinking

Abstract: Creative thinking ability development is needed to be implemented by every educator including lecturers to their students. Therefore, they need to seriously act and design their learning process. One of the ways to develop student's creative thinking is using discovery learning model. This research is conducted in physics education study program in 2016 with students who took learning and teaching class as research subject. From the research analysis result and discussion, it can be concluded that discovery le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
0
13
0
10
Order By: Relevance
“…For them, this model activates the students' thought processes. Furthermore, Rahman (2017) noticed that the use of discovery learning provides learners with the possibilities to develop creative thinking abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For them, this model activates the students' thought processes. Furthermore, Rahman (2017) noticed that the use of discovery learning provides learners with the possibilities to develop creative thinking abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies conducted on learners' critical thinking skills revealed that higher-order thinking required the teachers' careful planning and consideration (Fahmi et al, 2019;Gibson, 2012;Shirkhani & Fahmi, 2011;Tiwari et al, 2006). In this context, Rahman (2017) and Wahyudi, Rukmini and Bharati (2019) confirmed that discovery leaning is operative to stimulate the students' critical thinking and creativity. Likewise, Kusumawardani, Malya and Faizah 2019claimed that guided discovery learning-based activities promote learners' critical thinking skills.…”
Section: Guided Discovery For Promoting Critical Thinkingmentioning
confidence: 97%
“…Various studies conducted on learners' critical thinking skills revealed that higher-order thinking required the teachers' careful planning and consideration (Fahmi et al, 2019;Gibson, 2012;Shirkhani & Fahmi, 2011;Tiwari et al, 2006). In this context, Rahman (2017) and Wahyudi, Rukmini and Bharati (2019) confirmed that discovery leaning is operative to stimulate the students' critical thinking and creativity. Likewise, Kusumawardani, Malya and Faizah (2019) claimed that guided discovery learning-based activities promote learners' critical thinking skills.…”
Section: Guided Discovery For Promoting Critical Thinkingmentioning
confidence: 97%
“…Pada beberapa penelitian, peningkatan kemampuan bertanya siswa terbukti berkorelasi secara positif terhadap hasil belajar siswa (Nurazizah et al, 2019;Priyanto et al, 2018;Sastra et al, 2020). Strategi pembelajaran AdikSimba ini merupakan model pembelajaran Discovery Learning, dimana siswa dibimbing untuk memahami konsep, arti, dan hubungan melalui proses intuitif untuk mencapai suatu kesimpulan (Rahman, 2017). Dengan mengacu pada hal-hal tersebut, peneliti hendak mengetahui efektivitas penerapan metode Discovery Learning di SMP Negeri 5 Melaya dalam mengatasi permasalahanpermasalahan proses pembelajaran SMP Negeri 5 Melaya yang dievaluasi melalui peningkatan ketrampilan dan hasil belajar siswa.…”
Section: Pendahuluanunclassified